100 μj 100 kHz, CEP-stable high-power few-cycle fiber laser - Shestaev, E.; Hoff, D.; Hädrich, S.; Just, F.; Eidam, T.; Jójárt, P.; Várallyay, Z.; Osvay, K.; Paulus, Gerhard G.; Tünnermann, A.; Limpert, Jens (2019 Conference on Lasers and Electro-Optics Europe and European Quantum Electronics Conference, CLEO/Europe-EQEC 2019, 2019)
We present a CEP-stable Yb:fiber-based laser system delivering 100 μJ few-cycle pulses at the repetition rate of 100 kHz. The reported system is based on a highly scalable in terms of average power and pulse energy concept of a fiber chirped-pulse amplifier (CPA) combined with a hollow-core fiber compression stage. The same concept and similar components are employed by the ELI-ALPS HR1 [1].
CRIS-Team Scopus Importer:2023-04-20